Dinamika Politik Lokal Penggantian Calon Wakil Bupati Maros Pada Pilkada Kabupaten Maros Tahun 2024 - Muhammad Salman; Sukri Tamma; Ariana Yunus (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
The replacement of a deputy regent candidate in local political contests is not merely related to administrative procedures but also reflects the dynamics of power, legitimacy, and the political identity of an actor. This study aims to analyze local political dynamic in the replacement of the Maros Deputy Regent candidate during the 2024 Regional Head Election through the perspective of political identity and recognition. This article employs a qualitative method with data collection techniques based on media documentation and secondary data sources. The findings indicate that candidate replacement affects the political position, social legitimacy, and recognition experience of an actor who previously held the status of an incumbent deputy regent. The phenomenon also highlights the role of political elites and parties in determining access to political power. This study concludes that local political conflict occurs through processes of changing recognition, power distribution, and the negotiation of political identity.